ROMANTICISM AND SURREALISM IN THE DEPICTION OF "BAI YUN CANG" GOU - YONG, CHER WEL (unimas, 2017)
This study is about the Romanticism concepts and Surrealism subject matter especially in the modem art history and also in the context of contemporary arts. The research will study about the application of both concepts and subject matter respectively from different al1 movements in order to convey the message of "Bai Yun Cang Gou". By utilize this approach that had been identified and analyzed, a personal artwork has been created.